Design and Implementation of a New DELTA Parallel Robot in Robotics Competitions. (30th October 2015) - Lin, Jonqlan; Luo, Ci-Huang; Lin, Kao-Hui
This investigation concerns the design and implementation of the DELTA parallel robot, covering the entire mechatronic process, involving kinematics, control design and optimizing methods. To accelerate the construction of the robot, 3D printing is used to fabricate end-effector parts. The parts are modular, low-cost, reconfigurable and can be assembled in less time than is required for conventionally fabricated parts. The controller, including the control algorithm and human-machine interface (HMI), is coded using the Borland C++ Builder 6 Personal software environment. The integration of the motion controller with image recognition into an opto-mechatronics system is presented. The robot system has been entered into robotic competitions in Taiwan. The experimental results reveal that the proposed DELTA robot completed the tasks in those competitions successfully.